О НЕКОТОРЫХ ТЕРМИНОЛОГИЧЕСКИХ ПОНЯТИЯХ В ЭЛЕКТРОТЕХНИКЕ, СОДЕРЖАЩИХСЯ В СТАТЬЕ В.В. СОТНИКОВА («Технічна електродинаміка». 2017. № 3. С. 22–28) - Васецкий, Ю.М. (Інститут електродинаміки НАН України, Київ, 2018)
In this paper, in connection with various definitions in the literature, the concepts of "potential", "voltage", "voltage drop" are considered. Two approaches to the definition of the concept of " voltage " are analyzed: as the potential and as the work of the electric field forces on the displacement of a unit charge. Wrong and unreasonable positions in the paper by V.V. Sotnikov were noted. References 10.